LAC (Language Advisory Council) and CLI (Central Language Improvement) Efforts in Linguistic Activities in Improving the Speaking Skills of Tenth Grade Students in Preparation Class - Fadhilah, Rif'atul; Rochman, Abdul (Maharaat: Jurnal Pendidikan Bahasa Arab, 2024)
LAC (Language Advisory Council) is one of the centers to improve the linguistic abilities of students at the Muhammadiyah Islamic Boarding School, LAC also collaborates with one of the language organizations that is handled directly by OSPPM (Muhammadiyah Islamic Boarding School Student Organization). In this research, we investigate: 1) What are the efforts of the LAC and the central language department in improving speaking skills for linguistic activities in MBS Klaten? 2) Analyze the extent of the students in this activity. The objectives of this research are: 1) To analyze the efforts of LAC and the language part in lungistic improvement. 2) Analyze the extent of student improvement in this activity. The method used in this study was descriptive qualitative with the following writing steps: 1) Data Collection, 2) Data Analysis, 3) Conclusion. The results of this research are the preparation of language policies and curricula, supervision and preparation of programs, teacher training facilities and resource development.